Unraveling the Complexity of Critical Consciousness, Political Efficacy, and Political Action Among Marginalized Adolescents. Issue 1 (27th October 2015) - Diemer, Matthew A.; Rapa, Luke J.
Abstract : This research examines the complex patterns by which distinct dimensions of critical consciousness may lead marginalized adolescents toward distinct forms of political action. Structural equation modeling was applied to nationally representative data from the Civic Education Study (2, 811 ninth graders; M age  = 14.6), first establishing the measurement invariance of constructs across samples of poor or working class African American and Latino/a adolescents. Perceptions of societal inequality and aspirational beliefs that society ought to be more equal differentially predicted expected voting, conventional political action, and social action—while controlling for civic achievement and with nuances between ethnic and racial groups. Contrary to hypotheses and extant scholarship, political efficacy did not mediate or moderate relations between critical reflection and disparate forms of political action.